Hydatid cyst of thyroid gland, a rare case report with a literature review - Salih, Abdwlwahid M. (Int J Surg Case Rep, 2020)
INTRODUCTION: Although hydatid cysts can affect any organ in the body, reports regarding affection of thyroid gland are scanty in the literature. This report aims to present a case of thyroid hydatid disease with literature review. CASE REPORT: A 48-year-old female presented with painless anterior neck mass of about 2 year duration. There was an ill-defined, central anterior neck mass, with a smooth surface and mobile with deglutition. Ultrasound of the thyroid gland revealed an enlarged left lobe of thyroid gland due to well defined thick wall cystic nodule. The patient underwent left thyroid lobectomy under general anesthesia, the pathology report revealed hydatid cyst of thyroid gland. DISCUSSION: Liver and lungs are often the end destination for hydatid cysts, while other places like mediastinum, diaphragm, cardiac, smooth and skeletal muscles, abdominal and chest walls are rarely involved. In this case, the cyst affected even a rarer organ which was the left lobe of thyroid gland. Most of the time the disease is asymptomatic and is found accidentally, yet depending on the site and size of the cysts, symptoms can occur. CONCLUSION: Hydatid disease of thyroid gland is an extremely rare condition. The main presenting symptom is swelling. Operation under general anesthesia is the only modality of treatment.